Analysis of Factors That Influence Student Decisions in Choosing Politeknik Negeri Madiun as a Place of Study - Srimiatun; Utomo, Prasetyo Yekti; Setyawan, Dimas Ari (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
The aim of this research is to find out the most dominant factors that influence students' decisions in choosing Politeknik Negeri Madiun as a place of study. The research method used is a quantitative research method with a causality approach with the aim of Confirmatory Factor Analysis (CFA). The sampling method used in sampling was the Proportional Random Sampling method with a sample size of 220 respondents. The test results show that all indicators used to measure Psychological Factors, Cultural Factors, Price Factors and Promotional Factors are valid and reliable, whereas for Social Factors and Personal Factors each with three indicators, only two indicators are declared valid. The model has met the model goodness/fit test (Goodness of Fit)